Feasibility and Acceptability of Workers' Health Surveillance for Fire Fighters - Marie-Christine J. Plat; Monique H.W. Frings-Dresen; Judith K. Sluiter (Elsevier, 2011)
Objectives: The objective of this study was to test the feasibility and acceptability of a new workers' health surveillance (WHS) for fire fighters in a Dutch pilot-implementation project. Methods: In three fire departments, between November 2007 and February 2009, feasibility was tested with respect to i) worker intent to change health and behavior; ii) the quality of instructions for testing teams; iii) the planned procedure in the field; and iv) future WHS organisation. Acceptability involved i) satisfaction with WHS and ii) verification of the job-specificity of the content of two physical tests of WHS. Fire fighters were surveyed after completing WHS, three testing teams were interviewed, and the content of the two tests was studied by experts. Results: Feasibility: nearly all of the 275 fire fighters intended to improve their health when recommended by the occupational physician. The testing teams found the instructions to be clear, and they were mostly positive about the organisation of WHS. Acceptability: the fire fighters rated WHS at eight points (out of a maximum of ten). The experts also reached a consensus about the optimal job-specific content of the future functional physical tests. Conclusion: Overall, it is feasible and acceptable to implement WHS in a definitive form in the Dutch fire-fighting sector.